234k views
2 votes
X=y+3
4 = 3x - 2y
It’s substitution but I don’t know how to do it

User Brigham
by
5.3k points

2 Answers

1 vote
x= -2, y= -5

plug x=y+3 into the second equation
4= 3(y+3) -2y

solve for y
4= 3y+9 -2y
4=y+9
y= -5

plug y= -5 into either equation to get x
x= -5+3
x=-2
User BRBdot
by
5.7k points
6 votes

Answer:

4= 3(y+3) - 2y (substitute the given x-value into the equation to solve for y)

4= 3y+9-2y (use the distributive property)

4=y+9 (combine like terms)

y= -5 (subtract 9 from both sides to isolate the y-term)

plug it in

x= (-5)+3

x=-2

(-2,-5)

User Dundar Durma
by
5.4k points